HUBUNGAN INTERAKSI SOSIAL DENGAN PEMAHAMAN STRUKTUR RUANG PESERTA DIDIK SEKOLAH DASAR - Opermadia, Suci; Irawanis, Susi; Surya Elita, Ade; Arios; Sumanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between social interaction and spatial structure understanding among fourth-grade students at SDN 191/III Koto Cayo. Social interaction is a process of communication and cooperation among students that influences cognitive development, including the ability to understand spatial concepts in Social Studies (IPS) learning. Spatial structure understanding encompasses students' abilities to recognize and describe locations, distances, directions, and spatial patterns in their surrounding environment. The research method used was quantitative correlational with data collection techniques comprising social interaction questionnaires and spatial structure understanding tests. The population and sample of this study were all 30 fourth-grade students at SDN 191/III Koto Cayo. Data were analyzed using Pearson Product Moment correlation at a significance level of 0.05. The results showed a positive and significant relationship between social interaction and spatial structure understanding, with a correlation coefficient of r = 0.672 and p-value = 0.000 < 0.05. This means that the higher the intensity of students' social interaction, the better their understanding of spatial structure. The contribution of social interaction to spatial structure understanding was 45.2%. These findings imply that teachers need to design learning activities that encourage positive social interaction, such as group discussions, cooperation, and collaborative environmental exploration to improve students' spatial conceptual understanding.